2008
DOI: 10.1002/cbic.200800050
|View full text |Cite
|
Sign up to set email alerts
|

Efficient N‐Terminal Glycoconjugation of Proteins by the N‐End Rule

Abstract: Bulky amino acids in positions 2 and 3 of proteins protect both Met and noncanonical azidohomoalanine, introduced by the auxotrophy‐based method, from being excised by the enzymes responsible for N‐terminal Met excision. Bioorthogonal transformation enables new specific functionalization of target proteins. We validated this general concept by designing an N‐terminal glycoconjugated barstar capable of lectin binding without losing its biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
32
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 41 publications
4
32
0
1
Order By: Relevance
“…Thus far, azidohomoalanine (Aha) and homopropargylglycine (Hpg) have been incorporated using the native EcMetRS, [52,53] while azidonorleucine (Anl) [54] and propargylglycine (Pra) [51] were only translationally acive using mutants of EcMetRS. Especially, Aha and Hpg have been used to artificially attach to proteins post-translational modifications such as sugars [55] or biotin. [56] The recently developed BONCAT (bioorthogonal non-canonical amino acid tagging) strategy takes advantage of the incorporation of azidebearing ncAAs in the whole proteome and selective enrichment by affinity tags (e.g.…”
Section: Global Reassignment Of the Aug Codonmentioning
confidence: 99%
“…Thus far, azidohomoalanine (Aha) and homopropargylglycine (Hpg) have been incorporated using the native EcMetRS, [52,53] while azidonorleucine (Anl) [54] and propargylglycine (Pra) [51] were only translationally acive using mutants of EcMetRS. Especially, Aha and Hpg have been used to artificially attach to proteins post-translational modifications such as sugars [55] or biotin. [56] The recently developed BONCAT (bioorthogonal non-canonical amino acid tagging) strategy takes advantage of the incorporation of azidebearing ncAAs in the whole proteome and selective enrichment by affinity tags (e.g.…”
Section: Global Reassignment Of the Aug Codonmentioning
confidence: 99%
“…[9] In particular, substitution of the methionine residue by using the methionine auxotrophic strain, which results in methionine codon reassignment, is expected to provide practical N-terminal modification of proteins in vivo. The method was successfully employed to modify the N termini of target proteins in vivo with various bio-orthogonal reactive groups, [10][11][12] whereas most other approaches were limited to in vitro N-terminal modification. [13,14] The major problem of the methionine-residue-substitution method is that all of the methionine residues in the target protein are replaced by methionine surrogates; [15] this prevents N-terminal-specific modification.…”
mentioning
confidence: 99%
“…Hpg contains a bio-orthogonal alkyne group that can be used in the fluorescence labeling or glycosylation of proteins through Cu I -catalyzed cycloaddition. [11,35] The Supporting Information describes the procedure used for the incorporation of Hpg into MF-MscFv. SDS-PAGE analysis of the soluble fraction of cell extract confirmed that Hpg was incorporated into the MF-MscFv (Figure 4 A).…”
mentioning
confidence: 99%
“…We chose the structurally well-defined cysteine-free ''pseudo-wild-type barstar'' c-b* from Bacillus amyloliquefaciens as the protein scaffold. 16,19 c-b* is a 10 kDa protein composed of 90 amino acids with only one methionine residue. 19 The 3D-structure of parent c-b* 20 revealed three solvent-exposed positions (K23, E47 and K79) which were subsequently exchanged to methionine via sitespecific mutagenesis, giving rise to c-b*4M (Scheme 1).…”
mentioning
confidence: 99%
“…In this way, four alkyne-containing Hpg amino acids were efficiently introduced to c-b*4M by SPI yielding the congener denoted by c-b*4M [Hpg], which can be used to conjugate carbohydrates to barstar to four unnatural residues. 16,21 In addition, c-b*1M[Hpg] was expressed containing a single Hpg at the N-terminus for comparative lectin binding studies with mono-glycosylated barstar proteins.…”
mentioning
confidence: 99%